Electrocaloric properties and caloric figure of merit in the ferroelectric solid solution BaZrO3–BaTiO3 (BZT). Issue 2 (February 2021) - Novak, Nikola; Weyland, Florian; Jr, George A. Rossetti
Abstract: The impact of the differing phase change characteristics on the electrocaloric effect (ECE) and thermophysical properties of Ba(Zr x Ti1- x )O3 (BZT) were investigated. It is demonstrated that the ECE reduces strongly with increasing Zr concentration, from 1.25 K to 0.10 K. The strong reduction of ECE is associated with the vanishing of the latent heat as the nature of paraelectric to ferroelectric phase transition changes. Despite the second order nature of the phase transition, an enhanced electrocaloric responsivity, 0.225 × 10 −6 Km V -1, occurs at the triple point composition ( x = 0.13), where the stability fields of ferroelectric phases converge. The decreasing ECE and thermophysical properties with increasing Zr concentration result in a more than one order of magnitude reduction in a caloric figure of merit, from ∼3500 J m −1 s −1/2 to ∼200 J m −1 s −1/2 . The caloric figure of merit was used to compare the performance of other representative electrocaloric, magnetocaloric and mechanocaloric materials.